Nanostructure investigation of magnetic nanomaterial Ni 0.5 Zn 0.3 Cu 0.2 Fe 2 O 4 synthesized by sol-gel method - Pransisco, P. (American Institute of Physics Inc., 2015)
Magnetic nanomaterial Ni 0.5 Zn 0.3 Cu 0.2 Fe 2 O 4 was successfully prepared by using sol-gel method. Heat treatment on material is always giving defect on properties of material. This paper investigates the effect of heat treatment on nanostructure of magnetic nanomaterial Ni 0.5 Zn 0.3 Cu 0.2 Fe 2 O 4 . According to thermo gravimetric analysis (TGA) that after 600Â°C there is no more weight loss detected and it was decided as minimum calcination temperature. Intensity, crystallite size, structure, lattice parameter and d-spacing of the material were investigated by using X-ray diffraction (XRD). High resolution transmission electron microscope (HRTEM) was used to examine nanostructure, nanosize, shape and distribution particle of magnetic material Ni 0.5 Zn 0.3 Cu 0.2 Fe 2 O 4 and variable pressure field emission scanning electron microscope (VP-FESEM) was used to investigate the surface morphology and topography of the material. The XRD result shows single-phase cubic spinel structure with average crystallite size in the range of 25.6-95.9 nm, the value of the intensity of the material was increased with increasing temperature, and followed by lattice parameter was increased with increasing calcination temperature, value of d-spacing was relatively decreased with accompanied increasing temperature. From HRTEM result the distribution of particles was tend to be agglomerates with particle size of 7.8-17.68 nm. VP-FESEM result shows that grain size of the material increases with increasing calcination temperature and the surface morphology shows that the material is in hexagonal shape and it was also proved by mapping result which showing the presence each of constituents inside the compound. Â© 2015 AIP Publishing LLC.